2010
DOI: 10.1103/physrevb.82.184105
|View full text |Cite
|
Sign up to set email alerts
|

Grain growth and phase stability of nanocrystalline cubic zirconia under ion irradiation

Abstract: Grain growth, oxygen stoichiometry, and phase stability of nanostructurally stabilized cubic zirconia ͑NSZ͒ are investigated under 2 MeV Au-ion bombardment at 160 and 400 K to doses up to 35 displacements per atom ͑dpa͒. The NSZ films are produced by ion-beam-assisted deposition technique at room temperature with an average grain size of 7.7 nm. The grain size increases with irradiation dose to ϳ30 nm at ϳ35 dpa. Slower grain growth is observed under 400 K irradiations, as compared to 160 K irradiations, indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
90
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(96 citation statements)
references
References 26 publications
5
90
1
Order By: Relevance
“…Moreover, YSZ exhibits a very high radiation resistance, suggesting potential use as an IMF. This radiation resistance has been demonstrated in a series of experimental studies where the irradiation environment has been simulated with external ion beams [5][6][7][8][9][10][11][12] or also via computational approaches. [13][14][15] All works put forward that YSZ maintains its structural integrity up to very high irradiation levels ($100 displacements per atom, dpa).…”
Section: Introductionmentioning
confidence: 93%
“…Moreover, YSZ exhibits a very high radiation resistance, suggesting potential use as an IMF. This radiation resistance has been demonstrated in a series of experimental studies where the irradiation environment has been simulated with external ion beams [5][6][7][8][9][10][11][12] or also via computational approaches. [13][14][15] All works put forward that YSZ maintains its structural integrity up to very high irradiation levels ($100 displacements per atom, dpa).…”
Section: Introductionmentioning
confidence: 93%
“…Recently, it has been demonstrated that it is possible to produce nanocrystalline tetragonal or cubic zirconia that is thermodynamically stable at atmospheric pressures without the addition of stabilizers [10,13,14], i.e. they are nanostructurally stabilized.…”
mentioning
confidence: 99%
“…they are nanostructurally stabilized. Furthermore, the grain size of pure cubic nanostructurally stabilized zirconia (NSZ) films can be tailored by varying the ion dose during energetic, heavy ion irradiation [14]. Moreover, a significant loss of oxygen is also reported, suggesting the production of oxygen vacancies as a result of the irradiation [14].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…IBI is a feasible and efficient tool to investigate the radiation damage in nuclear materials. [2][3][4][5] Helium ion implantation was used to simulate a particle irradiation effects on materials considered for applications in fusion reactors. [6][7][8] Because the surface erosion of tungsten is the major concern in the fusion reactors, high flux, high fluence, and low energy (hundred eV) helium implantation was performed into tungsten at temperatures above 400 C. 9,10 Recently, in order to investigate the early stage of helium irradiation effect on tungsten, Lhuillier et al 7 performed irradiation with He ions of relatively low flux, low fluence and analyzed the corresponding microstructure of tungsten.…”
Section: Introductionmentioning
confidence: 99%